Pelatihan Metode Hafalan Al-Qur’an Bagi Santri Pemula di Taman Pendidikan Al-Qur’an (TPQ) Al Amin Sepit Kecamatan Keruak Lombok Timur - M. Ali Karmani (Pendidikan Al-Gafari, 2023)
The Qur’an Memorization Method Training for Beginner Students at TPQ Al Amin Sepit was motivated by the low memorization skills of the students and the limitations of teachers’ techniques, which still relied on traditional methods without a systematic structure. This training aimed to improve students’ memorization abilities, enhance teachers’ instructional skills, and increase students’ motivation and discipline. The method applied was participatory training involving five beginner students and three teachers, using observation sheets, teaching notes, and recitation recordings as instruments. Data were collected through direct observation, documentation, and brief interviews, then analyzed descriptively to identify developments in memorization, teaching techniques, and students’ motivation. The results indicated a significant increase in the number of verses memorized, from an average of 5,6 to 1,3,4 improvement in teachers’ instructional skills through the application of talaqqi, tikrar, chunking, and structured tasmi’ methods, and enhanced students’ motivation and discipline in reviewing their memorization both at TPQ and at home. The training effectively improved the quality of Qur’an memorization learning through systematic, structured, and participatory methods.